Black-White Disparities in Overweight and Obesity Trends by Educational Attainment in the United States, 1997–2008 - Chandra L. Jackson; Moyses Szklo; Hsin-Chieh Yeh; Nae-Yuh Wang; Rosemary Dray-Spira; Roland Thorpe; Frederick L. Brancati (Journal of Obesity)
Background. Few studies have examined racial and educational disparities in recent population-based trends. Methods. We analyzed data of a nationally representative sample of 174,228 US-born adults in the National Health Interview Survey from 1997 to 2008. We determined mean BMI trends by educational attainment and race and black-white prevalence ratios (PRs) for overweight/obesity (BMI > 25 kg/m2) using adjusted Poisson regression with robust variance. Results. From 1997 to 2008, BMI increased by ≥1 kg/m2 in all race-sex groups, and appeared to increase faster among whites. Blacks with greater than a high school education (GHSE) had a consistently higher BMI over time than whites in both women (28.3 ± 0.14 to 29.7 ± 0.18 kg/m2 versus 25.8 ± 0.58 to 26.5 ± 0.08 kg/m2) and men (28.1 ± 0.17 kg/m2 to 29.0 ± 0.20 versus 27.1 ± 0.04 kg/m2 to 28.1 ± 0.06 kg/m2). For participants of all educational attainment levels, age-adjusted overweight/obesity was greater by 44% (95% CI: 1.42–1.46) in black versus white women and 2% (1.01–1.04) in men. Among those with GHSE, overweight/obesity prevalence was greater (PR: 1.52; 1.49–1.55) in black versus white women, but greater (1.07; 1.05–1.09) in men. Conclusions. BMI increased steadily in all race-sex and education groups from 1997 to 2008, and blacks (particularly women) had a consistently higher BMI than their white counterparts. Overweight/obesity trends and racial disparities were more prominent among individuals with higher education levels, compared to their counterparts with lower education levels.